Accuracy of a foot temperature monitoring mat for predicting diabetic foot ulcers in patients with recent wounds or partial foot amputation. (March 2020) - Gordon, Ian L.; Rothenberg, Gary M.; Lepow, Brian D.; Petersen, Brian J.; Linders, David R.; Bloom, Jonathan D.; Armstrong, David G.
Highlights: Foot temperature monitoring is evidence-based and recommended clinical practice. It can enable early non-invasive interventions to prevent diabetic foot complications. Adoption may be limited by perceived challenges in some patients. Patients with recent wounds or partial foot amputations are perceived challenging. We report it is no less accurate in these patients, supporting more widespread use. Abstract: Aims: To assess the accuracy of once-daily foot temperature monitoring for predicting foot ulceration in diabetic patients with recent wounds and partial foot amputation, complications previously perceived as challenging. Methods: We completed a planned analysis of existing data from a recent study in 129 participants with a previously-healed diabetic foot ulcer. We considered four cohorts: all participants, participants with partial foot amputation, participants with a recent wound, and participants without partial foot amputation and without a recent wound. We reported the prediction specificity, lead time, and annualized alert frequency in each cohort at maximum sensitivity. We assessed the two potentially challenging cohorts for non-inferior accuracy relative to the control cohort using Delong's method. Results: We report non-inferior predictive accuracy in each of the two potentially-challenging cohorts relative to the control cohort (⍺ < 0.05). The alert lead time was similar across these cohorts, ranging from 33 to 42 days. Conclusions: Once-daily foot temperature monitoring is no less accurate for predicting foot ulceration in those with recent wounds and partial foot amputations than in those without these complications. These results support expanded practice of once-daily foot temperature monitoring, which may result in improved patient outcomes and reduced healthcare resource utilization.